We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
57
3
avatar

sqrt(75)-sqrt(12)-sqrt(27)

 Oct 21, 2019
 #1
avatar
+1

sqrt(75)-sqrt(12)-sqrt(27)=0

 Oct 21, 2019
 #2
avatar+153 
+1

Your answer is 0.

 

sqrt(75)-sqrt(12)-sqrt(27) = 0

 Oct 21, 2019
 #3
avatar+104969 
+1

√(75) -√(12) - √(27)  =

 

√[25 * 3]  - √ [ 4 * 3]   -  √ [ 9 * 3 ]    =

 

5√3   -  2√3  -  3√3  =

 

0

 

 

cool cool cool

 Oct 22, 2019

14 Online Users